Synthesis of Cassava Starch-Grafted Polyacrylamide Hydrogel by Microwave-Assisted Method for Polymer Flooding - Maudy Pratiwi Novia Matovanni; Sperisa Distantina; Mujtahid Kaavessina (Indonesian Journal of Chemistry, 2022)
Cassava starch-grafted polyacrylamide (CS-g-PAM) hydrogels were synthesized using a microwave-assisted method and K2O8S2 (KPS) as an initiator. In this study, we studied the influence of the amount of acrylamide and irradiation time on the properties of CS-g-PAM. The characterization of CS-g-PAM obtained was shown by Fourier-transform infrared (FTIR) and Scanning Electron Microscope (SEM) analysis. To predict the behavior of the samples under reservoir conditions, the properties of CS-g-PAM, such as swelling ratio, water-solubility, and viscosity were determined as a function of temperature, salt concentration, and aging time. The FTIR spectra and SEM analysis of the CS-g-PAM confirmed that the polyacrylamide chains were successfully grafted onto the cassava starch backbone. The results showed that the increasing amount of acrylamide and the longer irradiation time improved the properties of CS-g-PAM. Preparation of CS-g-PAM with 10 g of acrylamide and 180 s of irradiation time resulted in the highest grafting percentage and water solubility, which was 1565.53 and 96.06%, respectively. Its viscosity also exceeded 97% after 15 days of aging. The results showed that CS-g-PAM expressed properties such as good thickening, temperature resistance, and salt resistance according to reservoir conditions. This finding indicated that CS-g-PAM has good potential for oil recovery applications.